Application of fire safety at informal Islamic schools / Nur Syahirah Aznan and Mohd Zaki Shamsudin - Aznan, Nur Syahirah; Shamsudin, Mohd Zaki (2018)
Fire safety is a performance characteristic of buildings. The technological functions of fire safety systems interact with the systems that are necessary for other environmental control systems and to fulfill other performance characteristics expected from the building. For some aspects of fire safety, the systems need to generate the ambient environment and the control expected over the environment. Fire safety needs to be conceptually the same systems in order to control the environment that changes due to intrusion of products or combustion. The aim of the study was to investigate the applications of fire safety at Informal Islamic Schools. The result from the study shows that lower requirement of fire safety must be improved for the occupier’s safety which includes teachers and students.